Paisia, an Early Cretaceous eudicot angiosperm flower with pantoporate pollen from Portugal. Issue 1 (4th March 2018) - Friis, Else Marie; Mendes, Mário Miguel; Pedersen, Kaj Raunsgaard
Abstract: A new fossil angiosperm, Paisia pantoporata, is described from the Early Cretaceous Catefica mesofossil flora, Portugal, based on coalified floral buds, flowers and isolated floral structures. The flowers are actinomorphic and structurally bisexual with a single whorl of five fleshy tepals, a single whorl of five stamens and a single whorl of five carpels. Tepals, stamens and carpels are opposite, arranged on the same radii and tepals are involute at the base clasping the stamens. Stamens have a massive filament that grades without a joint into the anther. The anthers are dithecate and tetrasporangiate with extensive connective tissue between the tiny pollen sacs. Pollen grains are pantoporate and spiny. The carpels are free, apparently plicate, with many ovules borne in two rows along the ventral margins. Paisia pantoporata is the oldest known flower with pantoporate pollen. Similar pantoporate pollen was also recognised in the associated dispersed palynoflora. Paisia is interpreted as a possibly insect pollinated, herbaceous plant with low pollen production and low dispersal potential of the pollen. The systematic position of Paisia is uncertain and Paisia pantoporata most likely belongs to an extinct lineage. Pantoporate pollen occurs scattered among all major groups of angiosperms and a close match to the fossils has not been identified. The pentamerous floral organisation together with structure of stamen, pollen and carpel suggests a phylogenetic position close to the early diverging eudicot lineages, probably in the Ranunculales.